2021
DOI: 10.1093/ehjcvp/pvab053
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular outcomes with GLP-1 receptor agonists vs. SGLT-2 inhibitors in patients with type 2 diabetes

Abstract: Aims We examined cardiovascular outcomes associated with initiation of GLP-1RA versus SGLT-2i treatment in a real-world setting among patients with type 2 diabetes. Methods and Results This Danish nationwide registry-based cohort study included patients with type 2 diabetes with a first ever prescription of either GLP-1RA or SGLT-2i from 2013 through 2015 with follow-up until end of 2018. All analyses were standardized with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…In this meta-analysis we included 9 large PSM cohort studies (4)(5)(6)(7)(8)(9)(10)(11)(12). Each of included studies was assessed as high quality according to NOS.…”
Section: Resultsmentioning
confidence: 99%
“…In this meta-analysis we included 9 large PSM cohort studies (4)(5)(6)(7)(8)(9)(10)(11)(12). Each of included studies was assessed as high quality according to NOS.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed up to 2019 SGLT-2i could be prescribed only in patients with eGFR > 60 ml/min/1.73m 2 while GLP-1 RA in those with eGFR up to 30 and more recently up to 15 ml/min/1.73m 2 . To date, only Lugner et al investigated the renal composite outcome occurrence in GLP-1RA and SGLT-2i initiators, finding no significant differences between groups, even though point estimates for most kidney outcomes favoured SGLT-2i initiators [ 16 ]. Lugner et al enrolled a population with preserved renal function (eGFR > 90 ml/min/1.73m 2 ) [ 16 ], while the baseline eGFR of the patients included in the present study is unknown due to the use of claims data.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only Lugner et al investigated the renal composite outcome occurrence in GLP-1RA and SGLT-2i initiators, finding no significant differences between groups, even though point estimates for most kidney outcomes favoured SGLT-2i initiators [ 16 ]. Lugner et al enrolled a population with preserved renal function (eGFR > 90 ml/min/1.73m 2 ) [ 16 ], while the baseline eGFR of the patients included in the present study is unknown due to the use of claims data. Even though the proportion of patients with advanced and or acute renal disease at baseline was similar in the two cohorts according to the well-balanced PSM, we cannot exclude that SGLT-2i initiators could have had a better baseline renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our meta-analysis found no significant difference in the risk of composite cardiovascular outcome (HR 0.97, 95% CI 0.88-1.08, I 2 = 56%) or MACE (HR 0.96, 95% CI 0.84-1.08, I 2 = 46%) in type 2 diabetic patients treated with GLP-1RA vs. SGLT-2i (Figure 3A,B). Indeed, most real-world studies showed a similar effect of GLP-1RA vs. SGLT-2i on composite cardiovascular outcomes in patients at low cardiovascular risk [17,[30][31][32][33][34][35], with the exception of the study by Longato et al, in which a 22% reduction in the incidence of MACE over a median follow-up of 13 months in SGLT-2i vs. GLP-1RA users was noted (Table 2) [36]. The Authors found that the SGLT-2i benefit was particularly clear in patients with ascertained cardiovascular disease [36].…”
Section: Cardiovascular Outcomes In Real-world Studies Comparing Pati...mentioning
confidence: 98%